Analisis Kerentanan Masyarakat Pesisir Dalam Menghadapi Perubahan Iklim Di Desa Malaka Lombok Utara - Ahmad Jupri; Supardiono Supardiono; Lalu Aby Dujana; Nina Efayantika Masri; Al Ghazali; Desi Purnama Sari Ningsih; Irzafli Wahyu Ramdan (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2026)
Climate change poses significant challenges for coastal communities whose livelihoods depend heavily on environmental conditions. This study aims to analyze the vulnerability of coastal communities in Malaka Village, Pemenang District, North Lombok Regency, to climate change and identify the adaptation strategies they employ. Using a qualitative descriptive approach, data were collected through observations, in-depth interviews, and documentation. The results indicate that climate change has affected local communities through stronger winds and sea waves, declining fish catches, coastal ecosystem degradation, and economic losses, particularly in the fisheries and tourism sectors. Community adaptation efforts remain limited and are mainly based on traditional knowledge, such as adjusting fishing schedules. Government support and institutional involvement are still insufficient, especially in providing climate information and early warning systems. Local organizations, including the Turtle Conservation Community (TCC), contribute to conservation and environmental education, although their role has not fully addressed community adaptation needs. This study recommends strengthening community capacity through training, improving access to climate-related information, and enhancing collaboration among communities, government agencies, and non-governmental organizations. These efforts are essential to support community-based adaptation and promote climate-resilient coastal development.